MIKROENKAPSULASI MINYAK SAWIT MENTAH DENGAN PENYALUT MALTODEKSTRIN DAN ISOLAT PROTEIN KEDELAI - Reno Fitri Hasrini; Fransiska Rungkat Zakaria; Dede R. Adawiyah; Irma Herawati Suparto (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2017)
Microencapsulation techniques have been used to improve the stability of carotenoids and in the development of food fortification. The aim of this study was to determine the effect of the ratio of the coating material formulation (maltodextrin (MD) and soy protein isolate (SPI)) to the core material crude palm oil (CPO) on the physicochemical characteristics of the CPO microcapsules. Microencapsulation were carried out with ratios of coating material (MD:SPI = 2:1(w/w)) and CPO of 1:1.0, 1:1.2, 1:1.4, and 1:1.6 (w/w). The mixtures were homogenized at 12.000 rpm for 3 minutes and then spray dryed at inlet temperature of 180°C and outlet temperature at 80°C. The CPO microcapsules were analysed for yield, moisture content, solubility, and encapsulation efficiency. The results showed that the formulation ratio of 1:1.6 (w/w) was the best because it had the highest yield (20.12±0.02%), total carotenoids (295.2±0.32 µg/g) and encapsulation efficiency (59.95±1.50%). The best CPO microcapsules had spherical shape and smooth surface with an average size of microcapsules of 1-12 μm. The results of X-ray diffraction (XRD) showed that microcapsules were in crystalline state with crystallinity and amorphous value of 69.3 and 30.7%, respectively.